Seeing Stars: Matthew Effects and Status Bias in Major League Baseball Umpiring - Kim, Jerry W.; King, Brayden G (Management Science, 2014)
This paper tests the assumption that evaluators are biased to positively evaluate high-status individuals, irrespective of quality. Using unique data from Major League Baseball umpires' evaluation of pitch quality, which allow us to observe the difference in a pitch's objective quality and in its perceived quality as judged by the umpire, we show that umpires are more likely to overrecognize quality by expanding the strike zone, and less likely to underrecognize quality by missing pitches in the strike zone for high-status pitchers. Ambiguity and the pitcher's reputation as a “control pitcher” moderate the effect of status on umpire judgment. Furthermore, we show that umpire errors resulting from status bias lead to actual performance differences for the pitcher and team. Data, as supplemental material, are available at http://dx.doi.org/10.1287/mnsc.2014.1967 . This paper was accepted by Jesper Sørensen, organizations.